Relationship Marketing: Investigating the processes of creating and evaluating value - Baugh, Bev (2007)
The development and management of long term successful relationships, in a business to business context, is widely accepted within the relationship marketing literature to add value (Baxter and Matear, 2004). This dissertation examines relationship marketing in a relatively unexplored context, and explores value creation through the development, management and importantly evaluation of relationships within an education setting.